Helicobacter Pylori HP0175 Promotes the Production of IL-23, IL-6, IL-1β and TGF-β. (January 2013) - Amedei, A.; Munari, F.; Della Bella, C.; Niccolai, E.; Benagiano, M.; Bencini, L.; Cianchi, F.; Silvestri, E.; D'Elios, S.; Farsi, M.; Prisco, D.; Zanotti, G.; et al.
Helicobacter pylori infection induces a chronic gastric inflammatory infiltrate. This study was undertaken to evaluate the type of the innate immune responses elicited by the secreted peptidyl-prolyl cis-trans isomerase of H. pylori (HP0175). The cytokine production induced by HP0175 in neutrophils, and monocytes was evaluated. HP0175 was able to induce the expression of IL-23 in neutrophils, and monocytes, and IL-6, IL-1beta and TGF-beta in monocytes. These findings indicate that HP0175 is able to promote the activation of innate cells and the production of a cytokine milieu that may favour the development of Th17 response.